The Intra-Household Distribution of Administrative Burdens - Martin, Lucie (The Economic and Social Review, 2024)
There is little research on the gender distribution of administrative burdens in the household, and on its potential contribution to gender inequality. I use original survey data from 1,176 cohabiting UK adults to document gender differences in administrative burdens, focusing on time-use, well-being, and self-assessed responsibility for tasks across ten policy domains (e.g. health, tax and childcare). While there is no gender difference in total administrative time-use, there are differences in time-use and responsibility for specific domains, especially care work and finances. Being the primary earner does not fully explain this. Women report lower well-being during all tasks except childcare; their greater subjective time pressure partly explains this gap.